The Orbital Stability of Solitary Wave Solutions for the Generalized Gardner Equation and the Influence Caused by the Interactions between Nonlinear Terms. (20th June 2019) - Zhang, Wei-Guo; Ling, Xing-Qian; Li, Xiang; Li, Shao-Wei
Abstract : In this paper, the orbital stability of solitary wave solutions for the generalized Gardner equation is investigated. Firstly, according to the theory of orbital stability of Grillakis-Shatah-Strauss, a general conclusion is given to determine the orbital stability of solitary wave solutions. Furthermore, on the basis of the two bell-shaped solitary wave solutions of the equation, the explicit expressions of the orbital stability discriminants are deduced to give the orbitally stable and instable intervals for the two solitary waves as the wave velocity changing. Moreover, the influence caused by the interaction between two nonlinear terms is also discussed. From the conclusion, it can be seen that the influences caused by this interaction are apparently when0 < p < 4, which shows the complexity of this system with two nonlinear terms. Finally, by deriving the orbital stability discriminantd ′ ′ ( c ) in the form of Gaussian hypergeometric function, the numerical simulations of several main conclusions are given in this paper.